Establishment of a transient and stable transformation protocol of Nicotiana tabacum mediated by Agrobacterium tumefaciens - Méndez-Muñoz, Laura (2019)
Biotechnological tools such as genetic engineering and molecular biology are very advanced, allowing the development of systems based on the use of plant cells for the production of recombinant proteins, which allows the development of platforms for biopharmaceuticals, enzymes and secondary metabolites production. Transient and stable transformation, allow production of recombinant proteins. In this work a stable transformation of N. tabacum callus from the BY-2 commercial line and a wild one (T1) was performed. In addition, agroinfiltration assays were carried out using two techniques: by syringe and vacuum. In both cases, the transformation was mediated by Agrobacterium tumefaciens LBA4404 which carried the vector pCAMBIA 1303, containing the GFP and GUS marker genes, and a hygromycin resistance gene. The expression of green fluorescent protein was evaluated by fluorescence microscopy. Expression of the hygromycin and β-glucuronidase resistance genes were evaluated by PCR. As a result, high GFP expression and good transformation rates were obtained.